Preoperative globulin‐to‐albumin ratio predicts outcome after curative resection in patients with gastric cancer - Shimizu, Takayuki (Ann Gastroenterol Surg, 2018)
AIM: The globulin‐to‐albumin ratio (GAR) is useful for prognostication of patients with various cancers. However, the significance of GAR in gastric cancer (GC) remains unclear. Our purpose was to investigate the relationship between the GAR and outcome after curative resection in GC patients. METHODS: Three‐hundred and seventy‐six patients who had undergone curative resection for GC were retrospectively reviewed. Univariate and multivariate analyses using the Cox proportional hazard model were performed to detect clinical characteristics that correlated with overall survival (OS), and their cut‐off values were identified using receiver operating characteristic (ROC) curve analyses. Kaplan–Meier analysis and log‐rank test were used for comparison of OS and relapse‐free survival (RFS). RESULTS: Multivariate analysis using 17 clinical characteristics selected by univariate analyses revealed that GAR (>0.80/≤0.80) was significantly associated with OS (hazard ratio [HR], 2.305; 95% CI, 1.122‐4.735; P = 0.023), as well as lymph node metastasis (presence/absence) (HR, 2.417; 95% CI, 1.077‐5.426; P = 0.032), neutrophil‐to‐lymphocyte ratio (>2.7/≤2.7) (HR, 2.368; 95% CI, 1.138‐4.930; P = 0.002), and serosal invasion (presence/absence) (HR, 3.443; 95% CI, 1.048‐11.31; P = 0.042). Kaplan–Meier analysis and log‐rank test demonstrated that the OS and RFS of patients with a high GAR (>0.80) were significantly poorer than those with low GAR (≤0.80). CONCLUSIONS: The GAR is a useful predictor of postoperative outcome among GC patients undergoing curative resection.